Effectiveness of Topical Mangosteen Pericarp Extract Against Angiogenesis in Mice Exposed to Ultra Violet B - Anwar, Anis Irawan; Djawad, Khairuddin; Fitri, Elfa Wirdani (Pakistan Journal of Nutrition, 2016)
Exposure to ultraviolet B (UVB) can have an impact on the epidermis and dermis that triggers inflammatory processes that affect angiogenesis in the skin. Our study aimed to assess the effectiveness of mangosteen pericarp extract against angiogenesis in mouse skin after being exposed to UVB. This research was carried out with animals in the anatomic pathology laboratory of Hasanuddin University in Makassar. We used an animal experimental research design with a control group. A total of 24 mice were divided into the following 4 sample groups: normal group, UVB group, ethanol group and mangosteen group. In the mangosteen group, mangosteen pericarp extract with a concentration of 50% was smeared on the mice shortly after they were exposed to UVB. The amount of vascularization was significantly different among the groups. The greatest amount of vascularization was found in the ethanol group and the least amount was found in the normal group. The amount of vascularization in the mangosteen group was significantly lower than the UVB and ethanol groups but significantly higher than the normal group. In conclusion, the mangosteen pericarp extract concentration of 50% (2 mg/g of mouse weight) reduced the amount of angiogenesis, which is a marker of inflammation, in the skin of the mice that were exposed to UVB.